MARKETING MIX EXTENSION TO BOOST DISTRIBUTION PRODUCT OF CATFISH SHREDDED - Ristina Siti Sundari; Dona Setia Umbara; Andri Kusmayadi; Adnan Arshad (Comment: an International Journal of Community Development, 2019)
To success “Gemarikan” program such government’s design needed creativity along the process. One of creative process was shredded making. This way had a good prospect to be developed nevertheless the circulation of capital oftentimes stuck due to not sold completely but left in the market due to the consignation system ever. This community engagement aimed to increase Catfish shredded marketing to break capital and product circulation stuck dealing with ran well and sustainable business and also create new entrepreneur throughout Small and Middle Entrepreneurs in the county. The method used extension and implementation possible marketing mix. The result defined that producer was helped by these strategies for distributing, marketing catfish shredded faster than before deal with combining between direct selling, reselling and using market place of social media. In addition, the students begin to blaze the way to be an entrepreneur.